Experimental Analysis on Hairpin Curves - Paolo Discetti (The Baltic Journal of Road and Bridge Engineering)
The consistency of a highway alignment refers to the conformity of its geometry to driver expectancy and to the improvement of the design consistency and consequently it is necessary to know real speed behavior in order to calculate highway safety. The disparity between design and operating speeds has been shown, in fact several different studies were undertaken to predict the operating speed in different conditions as a function of the alignment features: horizontal and vertical curves, combinations of tangent sections of horizontal and vertical curves; sections prior to or following horizontal curves. In literature however, no studies speak of the operating speed on hairpin curves of mountain roads where driver behavior is influenced by the combination of small radius curves, limited sight distance and the approach to the slope of a tangent. Therefore, a mathematical model was developed specifically for mountain roads using speed data collected on hairpin curve and tangent approaches. The experimental study was carried out using traffic counters capable of recording the following variables during the passage of each vehicle in both directions: vehicle length, instant speed and direction. Video cameras were also used. In this paper the author also investigated the real speed driver behavior by analyzing deceleration and acceleration rates. These rates were calculated for each vehicle and then the 85th percentile of the rate distribution was also calculated. With the availability of acceleration and deceleration rates that respect real driver behavior, it is possible to analyze the defects of existing mountain roads and to evaluate corrective measures that can be implemented.